Parvoviral enteritis and salmonellosis in raccoons with sudden death. (November 2021) - Lin, Chun-Ming; Hause, Benjamin; Gualtieri, Deanna; Robinson, Nicholas
Eight of 9 juvenile raccoons at a rehabilitation center died without obvious prior clinical signs. Gross changes were unremarkable except for mildly distended intestines. Microscopically, crypt loss, distension, necrosis, and regeneration with intranuclear viral inclusions were observed in the small intestine, with marked lymphoid depletion and necrosis in Peyer patches and mesenteric lymph nodes. Immunohistochemistry with a canine parvovirus antibody showed intensive signals of parvoviral antigens in the crypts and lymphoid germinal centers. Metagenomic sequencing allowed assembly of a complete parvoviral genome with >99% identity to canine parvovirus 2a, as well as Salmonella enterica subsp. enterica . Also, S. enterica subsp. enterica serovar Thompson with multiple antimicrobial resistance was isolated from the intestinal contents. Concurrent infection with parvovirus and Salmonella should be included as a differential diagnosis in raccoons with sudden death.